Phosphorylated Platelet-Derived Growth Factor Receptor-Positive Cells With Anti-apoptotic Properties Accumulate in the Synovium of Patients With Rheumatoid Arthritis - Matsumura, Takashi; Saito, Yuki; Suzuki, Tomoyuki; Teramoto, Atsushi; Ozasa, Yasuhiro; Yamashita, Toshihiko; Fujimiya, Mineko; Saito-Chikenji, Takako (Frontiers in Immunology, 2019)
Rheumatoid arthritis (RA) is an autoimmune disease caused by inflammation of the synovium and characterized by chronic polyarthritis that destroys bone and cartilage. Fibroblast-like synoviocytes (FLSs) in the synovium of patients with RA can promote cartilage and bone destruction by producing proteins such as matrix metalloproteinases and receptor activator of NF-κB ligand, thereby representing an important therapeutic target for RA. FLSs have several phenotypes depending on which cell surface proteins and adhesion factors are expressed. Identifying the cellular functions associated with different phenotypes and methods of controlling them are considered essential for developing therapeutic strategies for RA. In this study, synovial tissue was collected from patients with RA and control subjects who required surgery due to ligament injury or fracture. Immunohistological analysis was used to investigate the rates of positivity for phosphorylated platelet-derived growth factor receptor-αβ (pPDGFRαβ) and cadherin-11 (CDH11) expression, and apoptosis-related markers were assessed for each cell phenotype. Next, FLSs were isolated in vitro and stimulated with tumor necrosis factor-α (TNF-α) in addition to a combination of PDGF and transforming growth factor (2GF) to investigate pPDGFRαβ and CDH11 expression and the effects of the inhibition of TNF and cyclin-dependent kinase (CDK) 4/6 on FLSs. Immunohistological analysis showed a large percentage of pPDGFRαβ+CDH11– cells in the sub-lining layer (SL) of patients with RA. These cells exhibited increased B-cell lymphoma-2 expression, reduced TNF receptor-1 expression, resistance to cell death, and abnormal proliferation, suggesting a tendency to accumulate in the synovium. Further, in vitro 2GF stimulation of FLSs lowered, whereas 2GF + TNF stimulation increased the pPDGFRαβ/CDH11 ratio. Hypothesizing that FLSs stimulated with 2GF + TNF would accumulate in vivo in RA, we determined the therapeutic effects of TNF and CDK4/6 inhibitors. The TNF inhibitor lowered the pPDGFRαβ/CDH11 ratio, whereas the CDK4/6 inhibitor suppressed cell proliferation. However, a synergistic effect was not observed by combining both the drugs. We observed an increase in pPDGFRαβ+CDH11– cells in the SL of the RA synovium and accumulation of these cells in the synovium. We found that the TNF inhibitor suppressed FLS activity and the CDK4/6 inhibitor reduced cell proliferation.